The use of language games in developing reading skills among primary school students from the perspective of teachers in Kuala Lumpur = استخدام الألعاب اللغوية في تنمية مهارة القراءة لدى طلاب المرحلة الابتدائية من وجهة نظر المعلمين في كوالالمبور: دراسة وصفية تحليلية - Husain Ahmad Mamat, Iman; Nasirudeen, Abdulwasiu Isiaq; Chtaibi, Khalid (Al-Madinah International University (MEDIU) Malaysia, 2026)
This study examines the use of language games in teaching Arabic reading skills among primary school students. It aims to explore the role of language games in developing reading skills from the perspectives of teachers in Arabic and international schools in Kuala Lumpur. The importance of this study stems from the growing need for modern teaching methods that consider the characteristics of young learners and enhance their motivation to learn. The study adopted a descriptive-analytical approach. Data were collected through structured interviews with a sample of twenty Arabic language teachers working at the primary school level. The data were analyzed using thematic analysis to identify the main themes related to the research questions. The findings revealed that the use of language games increases students’ engagement in reading activities and helps improve their comprehension and vocabulary development. However, teachers reported several challenges, including limited time, insufficient teaching resources, and weak internet access in some schools. The study recommends training teachers to design simple and effective language games that do not require internet access, as well as providing a supportive classroom environment that facilitates the use of these games in reading instruction. It also suggests integrating language games into school curricula to ensure their sustainable use and maximize their educational benefits in developing reading skills and enhancing students’ motivation to learn.